A Market Price for Organs?. Issue 2 (1st January 2013) - Thomas, Rick
Abstract Has not the time fully come to lift the prohibition on a regulated market in organs for transplantation? Is there a price for such a market that would be too high to pay? The author revisits the cases for and against organ markets in the light of cultural shifts in society and asks whether the traditional insistence on altruism represents a hindrance to much needed developments or a safeguard for much valued public goods.